Bayesian Analyses of Hume’s Argument Concerning Miracles - Levine, Michael (Philosophy & theology, 1997)
Bayesian analyses are prominent among recent and allegedly novel interpretations of Hume’s argument against the justified belief in miracles. However, since there is no consensus on just what Hume’s argument is any Bayesian analysis will beg crucial issues of interpretation. Apart from independent philosophical arguments—arguments that would undermine the relevance of a Bayesian analysis to the question of the credibility of reports of the miraculous—no such analysis can, in principle, prove that no testimony can (or cannot) establish the credibility of a miracle. Bayesian analyses of Hume’s argument are not analyses of Hume’s argument at all—but superfluous representations of it.